Infancia y política social en regiones de frontera: una mirada desde América Latina - Zsögön, Cecilia (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This work analyzes the capacity of social policy to make children´s rights operational in a peripheral cross-border region. The study focuses on the Triple Border region between Argentina, Brazil and Paraguay. One of the challenges for social policy is to transcend the national sphere to act on a transnational scale, necessary to account for the reality of the population in a deeply interlinked region. On the other hand, social policy is still anchored in a welfare perspective that considers persons as recipients of state aid, and not as subjects with agency. Finally, we address the indifference towards the subjectivity of children, which prevents the implemented actions from reversing the situation of vulnerability that made them necessary at first.